How political activity began: on countering the construction of the Gorky nuclear power plant for heat supply - A. A. Fomenkov (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the political history of the Gorky region during the years of perestroika, namely, such a significant aspect as opposition to the construction of the Gorky nuclear power plant of heat supply. The aim of the work is to identify the features of the manifestation of political opposition in Gorky. The tasks of the work are related both to the peculiarities of the work of the opponents of the Gorky nuclear power plant with public opinion, and in terms of creating structures independent of the state. It is stated that the level of political activity in the RSFSR was very active if it concerned the problem of nuclear safety.